Influence of processing parameters on nanomaterials synthesis efficiency by a carbothermal reduction process - Suman, Pedro Henrique [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Springer, 2011)
In this work, the influence of synthesis parameters on the synthesis efficiency of tin oxide nanomaterials was studied by using the carbothermal reduction method in a sealed tube furnace. The parameters were the starting material, temperature and time of synthesis as well as the gas flux. The starting material was tin dioxide mixed with carbon black in a molar proportion of 1.5:1 and 1:1. The temperature range was from 950 to 1,125 A degrees C with a step of 25 A degrees C, and the synthesis times used were 15, 30, 45, 60, 75, 90, and 120 min. Using optimum values of the above parameters, the gas flux was changed to verify its influence. After completion of the syntheses, we found a grayish-black material inside the tube which was characterized by X-ray diffraction and scanning electron microscopy. The results showed that the collected material is composed of nanobelts (with width around 60 nm) and disks that grew preferentially in the SnO phase. A model based on the oxide vapor pressure was proposed to evaluate the efficiency of the process, and the results showed good agreement between experimental data and the proposed model. Based on the results obtained, the best conditions to obtain a homogeneous material with 95% efficiency is using a starting material in the molar proportion Sn:C of 1.5:1, a temperature of 1,132 A degrees C for 75 min, and a N(2) gas flux of 80 sccm.
Keywords: Synthesis efficiency; Carbothermal reduction process; Tin dioxide; Nanobelts; Vapor pressure of oxides; Aerosols